Excitons in 2D perovskites for ultrafast terahertz photonic devices - Kumar, Abhishek (2020)
In recent years, two-dimensional (2D) Ruddlesden-Popper perovskites have emerged as promising candidates for environmentally stable solar cells, highly efficient light-emitting diodes, and resistive memory devices. The remarkable existence of self-assembled quantum well (QW) structures in solution-processed 2D perovskites offers a diverse range of optoelectronic properties, which remain largely unexplored. Here, we experimentally observe ultrafast relaxation of free carriers in 20 ps due to the quantum confinement of free carriers in a self-assembled QW structures that form excitons. Furthermore, hybridizing the 2D perovskites with metamaterials on a rigid and a flexible substrate enables modulation of terahertz fields at 50-GHz modulating speed, which is the fastest for a solution-processed semiconductor-based photonic device. Hence, an exciton-based ultrafast response of 2D perovskites opens up large avenues for a wide range of scalable dynamic photonic devices with potential applications in flexible photonics, ultrafast wavefront control, and short-range wireless terahertz communications.